Comparative pharmacokinetics and pharmacodinamics of noopept, its activity metabolite cycloprolylglycine and piracetam - Svetlana Boyko; Ksenia Kolyasnikova; Vladimir Zherdev (LLC "Publisher OKI", 2019)
While studing of experimental pharmacokinetics of the peptide analogues piracetam noopept - N-phenylacetyl-L-prolyl-glycine ethyl ester, was found the active metabolite that identificated as cyclo-L-prolylglycine (CPG). At that thime CPG was detected as the endogenous compound in plasma and brain. It was found that the pharmacokinetic parameters of CPG have the better characteristics than noopept and its prototype piracetam for the longer period of eliminations and the best bioavailability for the brain. It is found that the spectrum of nootropic and anxiolytic activity CPG and piracetam are composed. For piracetam also found antihypoxic and neuroprotective effects that were not investigated for CPG. Furthermore while studying of the pharmacological activity was found significant differences in the effective doses of comparable drugs that were no described by their different pharmacokinetics. This paper presents the results of comparative study of the antihypoxic and neuroprotective effects of CPG and piracetam in comparision wich pharmacokinetic parameters of studied compounds.